Sistem Kontrol Pada Penggunaan Energi Listrik Berbasis Android Studi Kasus : Sekolah Menengah Pertama Negeri (SMPN) 7 Pontianak - Riki Ruli A. Siregar; Alwi Baraqbah (Sekolah Tinggi Teknik - PLN, 2015)
Automation in daily life has now become a necessity which began to be used in all areas, especially in the fields of education, economics, business, and industry. In the field of education , especially in elementary school, junior high school and high school, almost all the schools in Indonesia do electronic equipment settings which should help school personnel work with ease but still in do with the complicated, for example, conventional job still turn on and off the buzzer and lights, open the gates still use human tools, turn on a fan that has not been controlled in the center and many problems are still to be done manually with the help of human hand. In this case there needs to be a system that can manage and monitor the places they live and conduct electricity in a sustainable management. Responding to the issue in this thesis was designed and fabricated an integrated device such as intelligent building control system based on Android that uses a microcontroller, network and webserver in control. By utilizing the wireless connection technology , Raspberry, Arduino is expected to work optimally so as to provide safety and comfort .